Psychological Adaptation among Students with Learning Disabilities in English from the Perspective of Their Teachers in Light of the Corona Pandemic - Mohamad Ahmad Saleem Khasawneh (Journal La Sociale, 2021)
The study identified the level of psychological adaptation of students with learning disabilities in English from their teachers’ perspectives. The study aims to achieve results to develop treatment programs for children with learning disabilities in English to help them move away from shyness, fear, and symptoms of social inadequacy in general and psychological adaptation in particular. It can also have a preventive value represented in discovering and assisting children who suffer from psychological maladaptation. The descriptive approach was used in this study and a questionnaire was developed as an instrument. Its validity and reliability were ensured and then applied to as ample of 30 teachers from Irbid city, Jordan, for the academic year 2019/2020. The results of the study indicated that there were statistically significant differences in the level of psychological adaptation among those with LDs in English from the point of view of their teachers. There were differences according to the gender variable in favor of females. In light of the results, the study recommends conducting scientific studies on psychological adaptation with variables other than the variables used in the research.